The Harmonization of Islamic Law and National Law on the Practice of Polygamy in Indonesia - Andrio Alex Nurdin; sayehu sayehu (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study aims to analyze the harmonization between Islamic law and national law in regulating the practice of polygamy in Indonesia. The main focus of this research is to examine how both legal systems interact in defining the limits, conditions, and objectives of polygamy so that it remains consistent with the principles of justice and public welfare. The research employs a library research method by reviewing classical and contemporary literature, Qur’anic exegesis, fiqh (Islamic jurisprudence) works, and relevant legal instruments, including Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). The findings reveal that, from the perspective of Islamic law, polygamy is not an obligation but a conditional permission that can only be practiced if the principle of justice can be upheld and family welfare ensured. Meanwhile, within the framework of national law, the principle of monogamy remains the fundamental rule; however, limited exceptions are allowed under strict legal procedures, such as obtaining court authorization, spousal consent, and proof of the husband’s financial capability. Both legal systems ultimately share the same objective to uphold justice, prevent misuse, and protect the rights of women and children. Therefore, the harmonization between Islamic law and national law in the practice of polygamy in Indonesia reflects an effort to integrate religious values with the principles of positive law within a unified framework of humanistic and civilized justice.